Adrenergic signaling during parasitic infections - Gardias, Patrycja; Bąska, Piotr (Frontiers in Immunology, 2026)
Adrenergic signaling plays a critical role in modulating immune and physiological responses during parasitic infections. Catecholamines such as adrenaline and noradrenaline interact with adrenergic receptors (ARs) to regulate immune cell activity, inflammation, and systemic processes. This review highlights the involvement of adrenergic pathways in infections caused by protozoa (Trypanosoma spp., Plasmodium spp., Toxoplasma gondii, Leishmania spp.) and helminths (cestodes, nematodes, and flukes). Central nervous system invasion by parasites is associated with neurodegeneration, mediated by immune and adrenergic mechanisms. Dysregulation of adrenergic signaling can exacerbate infection outcomes or contribute to immune-mediated tissue damage. Understanding these mechanisms provides insights into the potential of targeting adrenergic pathways to improve therapeutic strategies and manage parasitic infections effectively.